Recombinant human plasma phospholipid transfer protein (PLTP) to prevent bacterial growth and to treat sepsis - Valérie Deckert (Nature Portfolio, 2017)
Abstract Although plasma phospholipid transfer protein (PLTP) has been mainly studied in the context of atherosclerosis, it shares homology with proteins involved in innate immunity. Here, we produced active recombinant human PLTP (rhPLTP) in the milk of new lines of transgenic rabbits. We successfully used rhPLTP as an exogenous therapeutic protein to treat endotoxemia and sepsis. In mouse models with injections of purified lipopolysaccharides or with polymicrobial infection, we demonstrated that rhPLTP prevented bacterial growth and detoxified LPS. In further support of the antimicrobial effect of PLTP, PLTP-knocked out mice were found to be less able than wild-type mice to fight against sepsis. To our knowledge, the production of rhPLTP to counter infection and to reduce endotoxemia and its harmful consequences is reported here for the first time. This paves the way for a novel strategy to satisfy long-felt, but unmet needs to prevent and treat sepsis.